Corporate Entrepreneurship and the Pursuit of Competitive Advantage - Covin, Jeffrey G.; Miles, Morgan P. (Entrepreneurship Theory and Practice, 1999)
This paper presents a theoretical exploration of the construct of corporate entrepreneurship. Of the various dimensions of firm-level entrepreneurial orientation identified in the literature, it is argued that innovation, broadly defined, is the single common theme underlying all forms of corporate entrepreneurship. However, the presence of innovation per se is insufficient to label a firm entrepreneurial. Rather, it is suggested that this label be reserved for firms that use innovation as a mechanism to redefine or rejuvenate themselves, their positions within markets and industries, or the competitive arenas in which they compete. A typology is presented of the forms in which corporate entrepreneurship is often manifested, and the robustness of this typology is assessed using criteria that have been proposed for evaluating classificational schemata. Theoretical linkages are then drawn demonstrating how each of the generic forms of corporate entrepreneurship may be a path to competitive advantage.